2020
DOI: 10.2118/201105-pa
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Complex Fracture Propagation Under Temporary Plugging Conditions in a Naturally Fractured Reservoir

Abstract: Summary Temporary plugging during fracturing operations has become an efficient method to create a complex fracture network in tight reservoirs with natural fractures (NFs). Accurate prediction of the network-propagation process plays a critical role in plugging- and fracturing-parameter optimization. In this paper, the interaction between one single hydraulic fracture (HF) within a temporary plugging segment and multiple NFs was simulated using a complex fracture-development model. A new openin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Lu et al (2020) conducted a numerical simulation using a complex fracture development model where the interaction between one single hydraulic fracture within a temporary plugging segment and multiple natural fractures was observed. The numerical results demonstrated that the opening and development of a natural fracture are mainly dominated by its approaching angle and relative location [13].…”
Section: Relationship Between Hydraulic Fractures and Natural Fracturesmentioning
confidence: 93%
See 2 more Smart Citations
“…Lu et al (2020) conducted a numerical simulation using a complex fracture development model where the interaction between one single hydraulic fracture within a temporary plugging segment and multiple natural fractures was observed. The numerical results demonstrated that the opening and development of a natural fracture are mainly dominated by its approaching angle and relative location [13].…”
Section: Relationship Between Hydraulic Fractures and Natural Fracturesmentioning
confidence: 93%
“…An increasingly important segment of the industry is currently stimulating naturally fractured formations (e.g., tight sands and shales); where the assumptions of linear elasticity, simple fluid leakoff, and planar geometry fail to hold [10][11][12][13][14][15]. Temporary plugging during fracturing operations has become an efficient method to create a complex fracture network in tight reservoirs with natural fractures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, it is difficult to achieve the economic and efficient development of shale oil and gas resources. Therefore, the secondary reservoir stimulation is required to improve the fracture complexity and increase the stimulation volume, accordingly increasing the production in a single well [3,4]. The temporary plugging fracturing is an important technique to improve the fracture network stimulation efficiency of the re-fracturing in shale reservoirs [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate goal is to adequately divert the stimulated fluids into the reservoir (Erbstoesser, 1980). One major obstacle that limits the success of temporary plug fracturing technology has been the inability to use a ball sealer to seal the targeted perforation hole at the exact moment (Li et al, 2020;Lu et al, 2019). Hence, it is urgent to study the entire movement process and seating performance of ball sealers after their descent into the wellbore.…”
Section: Introductionmentioning
confidence: 99%